Targeting DNA Damage Repair Deficiency in Pancreatic Cancer - Stoof, Jojanneke (Trinity College Dublin. School of Medicine. Discipline of Surgery, 2024)
Pancreatic ductal adenocarcinoma is a lethal disease with a 5-year survival of <12%. Approximately 5-10% of the patients have BRCA1/2 mutations which cause homologous recombination (HR) deficiency and sensitise to cisplatin and PARP inhibitors (PARPi). However, intrinsic and acquired resistance are common and not well understood. Lack of representative in vitro models is a challenge in treatment development, and research is shifting from the use of 2D monolayer cultures to more representative 3D spheroid and organoid cultures. Yet, the effect of culture method on drug sensitivity remains largely unexplored. In this thesis, I developed six isogeneic 2D and 3D models and investigated their sensitivity to cisplatin, olaparib, and talazoparib. I observed significant differences in sensitivity between the isogeneic models, but sensitivity did not correlate with culture method which highlights the importance of using multiple models to test drugs. Additionally, I developed and characterised four novel patient-derived organoids from rare periampullary adenocarcinomas that are suitable for toxicity assays. To investigate the mechanism of acquired platinum and PARPi resistance, I developed cisplatin (Capan-1CisR) and PARPi (olaparib, Capan-1OlaR; and talazoparib, Capan-1TalR) mtBRCA2 Capan-1 cells. Resistant cells had significant cross-resistance to PARPi and oxaliplatin, but not to 5-FU or gemcitabine, suggesting that 5-FU and gemcitabine may be effective second-line treatments. The resistant cells had significant metabolic alterations which may contribute to resistance. Interestingly, the metabolomic profile of Capan-1OlaR was different from that of Capan-1CisR and TalR, suggesting a different mechanism of resistance. To investigate if loss of other DNA damage repair genes can also sensitise to PARPi, I performed two CRISPR/Cas9 knockout screens which identified PTEN, BRCC3, and XRCC3 as potential targets. Validation by siRNA knockdown in a viability assay confirmed synthetic lethality. Additionally, I investigated if the combination of ATM or ATR inhibitor with PARPi can overcome resistance in the previously developed resistant Capan-1 cells. Combination of ATRi (Ceralasertib) and PARPi (Lynparza and Saruparib) was synergic in the parental and olaparib-resistant Capan-1 cells, suggesting that Ceralasertib may help to prevent or overcome olaparib-resistance in the clinic.
APPROVED
Keywords: cancer; pancreatic ductal adenocarcinoma; organoids; CRISPR; resistance; chemotherapy; PARP inhibitors; DNA damage repair